State Elementary School Principles as Opinion Leaders in The Disruptive Era - Kamaludin (International Journal of Education and Humanities, 2022)
Principals play an important role in the development and improvement of the performance of teachers and educational staff at the individual level and organizational levels. Principal leadership must be structurally integrated within the organization. This is to ensure the achievement of the vision and mission set by the school. In the current era of digitalization, school principals not only play a role in inclusive, distributive leadership, and encourage leadership capacity building within schools but also play a role as opinion leaders. This study uses a qualitative approach with exploratory research. The main focus of research is the principal of public elementary schools as opinion leaders in the disruptive era. Principals of 15 public primary schools with at least five years of experience were the subject of this study. This research was conducted between May and August 2022. The research location is in Brebes Regency, Central Java. The results of the study show that the principal as an opinion leader is tasked with introducing innovations and through persuasive or coercive actions taking policies to accelerate the use of innovations in education.